The nucleotide sequence of 5S rRNA from a red alga, Porphyra yezoensis. - Takaiwa, F (1982)
The nucleotide sequence of 5S rRNA from Porphyra yezoensis has been determined to be: pACGUACGGCCAUAUCCGAGACACGCGUACCGGAACCCAUUCCGAAUUCCGAAGUCAAGCGUCCGCGAGUUGGGUUAGU - AAUCUGGUGAAAGAUCACAGGCGAACCCCCAAUGCUGUACGUC. This 5S rRNA sequence is most similar to that of Euglena gracilis (63% homology).